Identification of microorganisms producing lactic acid during solid‐state fermentation of Maotai flavour liquor. Issue 1 (20th November 2018) - Yang, Fan; Chen, Liangqiang; Liu, Yanfeng; Li, Jianghua; Wang, Li; Chen, Jian
Abstract : Lactic acid is the main acid produced during the Maotai liquor brewing process, influencing the quality of the base liquor and fermentation process. However, the microorganisms responsible for lactic acid production have not been identified. In this work, the dynamic changes in bacterial community structure in the Zaosha round (second sorghum feeding and fermentation) of the brewing process were analysed by 16S rRNA high‐throughput sequencing. Results show that lactic acid bacteria (LAB) and Bacillus spp. are the dominant bacteria in the brewing process, where Bacillus spp. are found in the early stage, whilst LAB are found throughout the brewing process. Furthermore, 10 types of LAB and five Bacillus spp. were isolated from Zaopei (a mixture of fermented grains including sorghum and wheat) by a culture‐dependent method. Lactobacillus panis accounts for 68% of the LAB, and Bacillus amyloliquefaciens for 54% of Bacillus spp. Solid‐state fermentation experiments were performed with L. panis and B. amyloliquefaciens and lactic acid production was consistent with the accumulation of lactic acid in Zaosha . The results showed that L. panis was the main producer of lactic acid in pits, while B. amyloliquefaciens plays an important role in the production of lactic acid in the early stages of fermentation. The approach used in this study may facilitate the identification of key microorganisms with specific functionality involved in other food and beverage fermentation processes. © 2018 The Institute of Brewing & Distilling